Exchequer motor game enhances geometric thinking and mood in first grade children - Aymen Hawani; Anis ben Chikha; Wael Zoghlami; Santo Marsigliante; Antonella Muscella (Discover Education)
Abstract This study investigated the effect of the motor game 'Exchequer Motor Game' (EMG) on first-grade children's Level of Geometric Thinking (LGT) and their post-learning mood tracking (PLMT). Thirty children (age 6.1 ± 0.7 years; physical education experience: 0.6 ± 0.4 years), classified at the “Visualization” stage of van Hiele’s geometric thinking, were randomly assigned to two groups. Both groups engaged in the EMG and the Conventional Geometry Course (CGC) in a counterbalanced, randomized cross-over design. LGT and PLMT were measured for all participants after the intervention using the Van Hiele Geometry Test (level 1) and a mood chart. Statistical analyses showed a significant increase in LGT after EMG (p < 0.05, Hedges'g = − 0.91, large effect) compared to that recorded after CGCwith a significant increase in LGT scores when switching from CGC to EMG (p < 0.001) and a significant decrease in scores when switching from EMG to CGC. Similarly, the PLMT was significantly higher after the EMG session than after the CGC session (p < 0.001) with significant increases in PLMT scores when switching from CGC to EMG (p < 0.001) and significant decreases when switching from EMG to CGC. Therefore, the results of the study suggest that practicing the EMG can positively contribute to improving the level of children's geometric thinking.